Mice transgenic for NPM-ALK develop non-hodgkin lymphomas - Jäger, Richard; Hahne, Jens Claus; Jacob, Andrea; Egert, Angela; Schenkel, Johannes; Wernert, Nicolas; Schorle, Hubert; Wellmann, Axel (Anticancer research, 2005)
Background: The t(2;5)(p23;q35) translocation is associated with a high percentage of anaplastic large-cell lymphomas (ALCL) of T- or null-cell phenotype. The translocation produces an 80 kDa hyperphosphorylated chimeric protein (p80) derived from the fusion of the anaplastic lymphoma kinase (ALK) with nucleophosmin (NPM). The NPM-ALK chimeric protein is an activated tyrosine kinase that has been shown to be a potent oncogene and presumably plays a causative role in lymphomagenesis. Materials and Methods: A transgenic mouse line was generated, where the human NPM-ALK cDNA is driven by the lck promoter conferring transgene expression to early T-cells. Results: Mice rapidly developed large cell lymphoblastic lymphomas with a median latency of 8 weeks, primarily involving the thymus, with lymph node as well as histologically evident extranodal organ infiltration by large tumor cells. Conclusion: The transgenic approach described provides direct evidence for the strong transforming potential of NPM-ALK in T-cells and furthermore represents a system for the analysis of the oncogenic events mediated by NPM-ALK in vivo, which might be instrumental in the development of tyrosine kinase inhibitor therapies of potential clinical use.